Design and Preliminary Testing of a Soft Exosuit for Assisting Elbow Movements and Hand Grasping - Xiloyannis, Michele (2016)
Most of the currently available exoskeletons for upper limbs are constrained by limited portability, ergonomics, weight and, energy-wise, autonomy. Moreover, their high cost makes them available only for the most affluent users, ruling out the majority of the population in need. By replacing rigid aluminum links and transmissions with fabrics and bowden cables, we can both cut down the cost of the assistive device and design it to be portable, comfortable and lightweight. We present the design and a preliminary testing of a soft exosuit for assisting elbow flexion/extension and hand open/close. Our system comprises two proximally located tendon-driving actuators, and two textile-based frames that route the tendons and transmit forces to the human joints, namely an elbow sleeve and a glove. A preliminary test on a healthy subject is presented with an adaptive controller that achieves good tracking accuracy despite of the system’s non-linear and time-varying dynamics.